EFEKTIFITAS SISTEM PENYAMPAIAN SURAT PEMBERITAHUAN (SPT) TAHUNAN PAJAK PENGHASILAN (PPh) MELALUI e-FILING DI KANTOR WILAYAH DIREKTORAT JENDERAL PAJAK JAWA TENGAH II - Haris, Abdul; ., Istifah (Kiat Bisnis, 2015)
One of the biggest sources of state revenue derived from the tax sector. Tax revenue is used to finance government expenditures, construction, as well as to improve the welfare of the community through increased public facilities. In order to improve the quality of the tax service to taxpayers, Direktort General tax reform in the field of tax administration, namely in the framework of the implementation of the type of service delivery and the delivery of the Notice to the Annual Tax Extension and conducted electronically through the online system or so-called e-filing. With the implementation of this system, the delivery of the Notice is expected to be more effective and efficient. The purpose of this study is to measure how the effectiveness of the delivery system of annual income tax returns via e-filing in the Office of the Directorate General of Taxation, Central Java II. This study used qualitative methods. Data was collected through interviews, documentation, and literature study. The level of effectiveness of the delivery system through the Annual Income Tax e-filing is measured in two ways: using the ratio of effectiveness, and comparing the number of individual taxpayers registered with the number of individual taxpayers who use the e-filing. Based on the research results, it can be concluded that the implementation of e-filing in 2013 is classified in the category are not effective with effectiveness ratio of 0.21% and the ratio between the number of individual taxpayers registered with that use e-filing by 0.12%..Keywords : effectiveness, Notice, e-filing